Understanding Teacher Reality Shock: A Systematic Bibliometric Review - Karabatak, Songül; Alanoğlu, Müslim; Kuloğlu, Ayşenur (My University, 2025)
This study investigated Teacher Reality Shock (TRS), referring to the challenges novice teachers encounter during their early career years, through bibliometric analysis. A total of 59 studies obtained from the Web of Science database via keyword searches for “reality shock” and “teacher” were analyzed using performance analysis and scientific mapping techniques. Results revealed a steady rise in TRS research between 1987 and 2024, with a notable increase after 2011. Key themes in the literature include beginning teachers, burnout, job satisfaction, self-efficacy, and occupational socialization. The United States and Germany are leaders in TRS research, while Turkey, despite recent progress, lacks substantial international impact. Current studies mainly focus on individual and organizational factors, highlighting gaps in understanding teachers’ self-efficacy, professional experiences, and cross-cultural comparisons of TRS. To address these gaps, interdisciplinary research and programs supporting teachers’ adaptation to their careers are essential. This study underscores the importance of incorporating TRS into teacher training policies to improve early-career teacher support and professional development.
Keywords: Teacher Reality Shock; Beginning Teachers; Early-Career Teachers; Bibliometric Analysis in Education